Halal Lifestyle Sebagai Wajah Islam Al-Wasathiyah : (Studi Kasus Pada Industri Makanan Halal) - Dian Luthvita Nadila; Nur Fitri Islamawati; Zulafa Maulania Agta Dhiyanda (CV. ULIL ALBAB CORP, 2023)
Nowadays there is a widespread radical understanding that leads to religion, especially Islam. On the other hand, halal lifestyle was born as a result of the 4.0 industrial revolution. The emergence of Islamic radicalism and halal lifestyle simultaneously became anxieties for the people which later led to the notion that halal lifestyle is a manifestation of radical Islam. The purpose of this study is to show that halal lifestyle is not a manifestation of Islamic radicalism, but a manifestation of Islam Al-Wasathiyah (Moderate). This research focus on the halal food industry is assessing various aspects, namely: health, social community, and intelligence. The method used in this study is the literature review. Based on the results of research it can be concluded that halal standards can be a universal standard for all people, so not only muslims can apply halal standards, but non-Muslims can also be part of this halal lifestyle. This shows that the halal food industry can be one of the manifestations of Islam rahmatan lil ‘alamin.